Analysis of Corporate Reputation as an Intervening Variable in the Relationship Between the Influence of E-Recruitment, Employer Branding, and Compensation on the Interest of Generation Z in Applying for Jobs - Salsabila, Sherlynda Febriana; Achmad, Nur (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: Generation Z, born between 1997 and 2012, grew up in the digital era and is highly familiar with the internet and online platforms. This study aims to determine the influence of E-Recruitment, Employer Branding, and Compensation on Generation Z's interest in applying for jobs, as well as the mediating role of Corporate Reputation in the relationship between Employer Branding and Generation Z's job application interest. Methodology: The population of this study consists of Generation Z in the city of Surakarta, with a sample of 385 respondents selected using Cochran's formula. The study employed an online questionnaire via Google Forms, distributed to Generation Z individuals in Surakarta who are either currently seeking jobs or planning to do so in the near future. Data analysis techniques included descriptive analysis using JASP and Structural Equation Modeling (SEM) analysis using Smart PLS 4. Results: The analysis reveals that E-Recruitment has a positive and significant impact on Generation Z's interest in applying for jobs. Employer Branding also demonstrates a positive and significant effect on Generation Z's job application interest. Additionally, Employer Branding significantly influences Corporate Reputation. However, Compensation does not have a significant effect on Generation Z's interest in applying for jobs. Similarly, Corporate Reputation does not significantly affect Generation Z's job application interest. The impact of Employer Branding on Generation Z's job application interest, mediated by Corporate Reputation, shows a negative and insignificant effect. Applications/Originality/Value: This study provides insights for companies in developing more effective recruitment strategies to attract high-achieving Generation Z talent.